Low-temperature and highly sensitivity H2S gas sensor based on ZnO/CuO composite derived from bimetal metal-organic frameworks. Issue 10 (July 2020) - Wang, Xu; Li, Sihan; Xie, Lili; Li, Xia; Lin, Donghai; Zhu, Zhigang
Abstract: The bimetallic metal-organic frameworks (MOF) Zn/Cu-BTC were prepared by a facile solvothermal method in one step and used as a self-sacrificed template to obtain the ZnO/CuO composites. The composites with different Cu/Zn molar ratios were characterized by XRD, FESEM, and XPS. The ZnO/CuO composite exhibited an octahedral structure, and a p-n heterojunction may be formed between p-type CuO and n-type ZnO. To prove its functional characteristics, the ZnO/CuO composite was used as a sensing material to test its gas sensitivity. The effect of Cu/Zn molar ratios was examined, and the results showed that the optimized ZnO/CuO (1: 0.33) composite based gas sensor exhibited reasonable selectivity to 10 ppm H2 S, operated at 40 °C. The sensitivities were improved by 17.1 times and 327.8 times compared with the pristine CuO and ZnO based gas sensors, respectively. Moreover, the detection limit to H2 S of such sensors could be reduced as low as 300 ppb. The sensing mechanism has been thoroughly studied and such ZnO/CuO composite is an ideal candidate for highly sensitive detection for H2 S with low power consumption in the real application. Highlights: Preparation of bimetallic MOF and ZnO/CuO composite using this as a self-sacrifice template. ZnO/CuO composite based gas sensors have superior response to H2 S at low operating temperature. ZnO is distributed on octahedral-like ZnO/CuO and plays a catalytic role. The formation of p-n junction in the ZnO/CuO composite take the key role in the enhancement of sensing performance.